The increasing big gap of carbon sink between the western and eastern Pacific in the last three decades - Zhong, Guorong; Li, Xuegang; Song, Jinming; Qu, Baoxiao; Wang, Fan; Wang, Yanjun; Zhang, Bin; Tian, Detong; Ma, Jun; Yuan, Huamao; Duan, Liqin; Li, Ning; et al. (Frontiers in Marine Science, 2022)
In this paper, the sea-air CO2 flux in the Pacific Ocean from 1992 to 2020 was reestimated using the gridded surface ocean pCO2 product constructed by the stepwise FFNN algorithm. The results show that the average CO2 flux of the Pacific Ocean was -0.73±0.17 PgC yr-1, with a -0.72±0.18 PgC yr-1 in the western Pacific and a -0.01±0.16 PgC yr-1 in the east. The stronger carbon sink in the western temperate Pacific and the stronger carbon source in the eastern equatorial Pacific led to a great west-east difference in CO2 flux, which decreased temporarily during the El Nino events and increased significantly in the last three decades. The western Pacific carbon sink strengthened from -0.56±0.17 Pg C yr-1 in 1992 to -0.78±0.18 Pg C yr-1 in 2020, occupying 35% and 36% of the global ocean CO2 uptake, respectively. The strengthening western Pacific carbon sink and relatively stable eastern Pacific carbon source led to an increasing west-east difference in CO2 flux from 0.41 Pg C yr-1 in 1992 to 0.73 Pg C yr-1 in 2020. However, the greater CO2 absorbed in the western temperate Pacific did not lead to a higher acidification speed than the east in the surface ocean, but was mainly transported toward deeper waters and caused a more significant carbon inventory change under the surface ocean than the eastern Pacific.